Pengaruh Sistem Akuntansi Pemerintah Daerah, Pengendalian Intern, Dan Transparansi Terhadap Akuntabilitas Kinerja Instansi Pemerintah Daerah Di Kabupaten Gresik - Kartika Dewi Anggraini; Nyimas Wardatul Afiqoh (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Government performance accountability, especially at the local level, is the main focus in responding to public demands. The implementation of performance accountability is believed to form a democratic government order, as evidenced in the Government Agency Performance Accountability Report. factors such as local government accounting systems, internal control systems, and transparency as key elements that influence performance accountability. The examination approach utilized is quantitative, which is a deliberate, coordinated, and organized research come nearer from the outset to the detailing of the exploration plan. The consequences of this study are that the Nearby Government Bookkeeping Framework altogether affects the exhibition of government organizations, as per the standards of Neighborhood Government Hypothesis. Interior Control doesn't make a huge difference, maybe because of varieties in execution in different neighborhood government settings. In any case, Straightforwardness fundamentally affects the adequacy of schooling program execution, as per the standards of Neighborhood Government which underline the significance of straightforwardness in spending plan the board. By and large, the free factors all the while fundamentally affect the exhibition responsibility of government organizations.Keywords: Local Government Accounting System; Internal Control; Transparency; Accountability of Local Government Agency Performance